A review: high power density motors for electric vehicles. (December 2020) - Sudha, B; Vadde, Anusha; Sachin, S
Abstract: The review of High Power Density Motor (HPDM) is presented, the high power density refers to ratio of output power to volume of the motor. As a result even a small envelope motor can have high power output. HPDM are also known as low speed high torque motors. The HPDM are compact, lightweight, has high torque and less cogging torque, finding application in automotive field, especially in electric and hybrid electric vehicles. This paper analyses the design, performance and efficiency of various HPDM. Comparative analysis of thirteen different HPDM are reviewed and tabulated for power density, speed, weight, rating and its applications.